Milk peptides; effect on the enzymatic hydrolysis of sodium caseinate - Haque, Zahur U.; Antila, Pirkko (Agricultural and Food Science, 1993)
Sodium caseinate (NaCN) was hydrolyzed using Rhozyme 41 (Rh41), Neutrase (Neu) and plasmin (PL) to obtain peptide preparations termed; Na-Cas-P-Rh41, Na-Cas-P-Neu, and Na-Cas-P-Plasmin, respectively. Indigenous whey peptides (IWP) were obtained from fresh sweet whey, at different levels of ufconcentration, by a precipitation method described earlier. These peptide fractions were then used to observe their effect on the activity of some proteases. All peptide preparations depressed enzyme activity. Na-Cas-P-Rh41 was the most powerful inhibitor of enzyme activity and decreased the activity of trypsin, Rh41, Neu. and PL by 15, 32, 50, and 14%, respectively. IWP markedly depressed activity of Rh41. The degree of uf-concentration of whey from which IWP was obtained was directly related to degree of inhibition.